Analisis Kesalahan Peserta Didik Dalam Menyelesaikan Soal Cerita Matematika Tentang Operasi Hitung Pecahan Kelas V Sekolah Dasar - Galuh, Sulistya; Kurniawan, Sandra Bayu; Budiharto, Tri (Didaktika Dwija Indria, 2022)
Abstract. This study aimed to (1) described the type of student error in solving fractional arithmetic operation story problem, (2) described the factor that cause student to made mistake in solving fractional counting operation story problem and, (3) described solution to correct student error in solving fractional calculation operation story problem. This research was a descriptive qualitative researched. The subject in this study was class V student and class V teacher at SD Negeri Setono. Data collection techniques used test question result, interview result, and observation. The data validity test technique used source triangulation technique. The data analysis technique used Miles and Huberman which includes 4 stages, namely: (1) data collection, (2) data reduction, (3) data presentation, (4) drawing conclusion. The results showed that the analysis of students' errors in solving story problem about calculating operations on error indicators interpreted mathematical symbols 8.90%, error in formulating a problem solving model 44.07%, transformation errors 9.26%, mathematical skill errors 14.81%, and final answer writing skills 22.96%. Based on the results of the study, it can be concluded that the analysis of student errors in solving story questions about fractional calculation operations on error indicators formulating a problem solving model was the most common indicator.